Practical application of DNA technology to support livestock breeding in southern Africa - Kotze, A.; Harris, E.J.; Soma, P.; Joubert, E. (TSAP and ILRI, 2006)
The development of molecular genetics, especially DNA technology, has created the opportunity for animal breeders to make use of the dramatic progress in agricultural biotechnology. The most applicable development in South Africa is DNA profiling. Through the analysis of unique banding patterns, applications such as individual identification, parentage verification, genetic characterisation and the detection of genetic defects and undesirable genes are performed. The results for the different farm animal species are stored in databases for reference. Parentage verification is determined very accurately and the results are used for the registration of animals. Direct information on the genotypes of polymorphic loci allows for the measurement of breed relationships. The screening of animals for genetic defects through the detection of single point mutations is discussed using examples from the dairy and pig industries. The use of DNA technology as a tool contributes to accurate information in breeding programmes that make use of genetically superior individuals while maintaining biological diversity.